COMPARATIVE EFFICIENCY OF TRAWLS MADE OF NYLON ,POLYETHYENE ,MONO FILAMENT AND TAPE TWINES. - KARTHA, K N; HRIDAYANATHAN, C; CECILY, P J (Fishery Technology, 2017)
Results cf comparative fishing operations conducted withthree nets of identical cesign made of nylon, twisted polye-1hylene monofilamenc and high ciensity polyethylene (HDPE)tape twines are presented in this communication. Since thetape net recorded the highest prawn and fish catch, monofilamentand nylon following in order, it can be recommended to thefishing industry as one of the cheapest and effective fishingmaterials evolved for trawl fabrication.